The relationship between mobile application usages towards job performance at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT) / Nor Farah Fadillah Nor Azmi - Nor Azmi, Nor Farah Fadillah (Faculty of Business and Management, 2018)
This research tried to discover the relationship between mobile application usages and job performance at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT) by establishing an integrated framework for mobile application usages and job performance. The first objective is to to investigate the relationship between every element of mobile application usages and job performance. Other objective is to discover the relationship between Mobile Application Usages and Job Performance. The process used is to collect data and information for the purpose of accomplishing the whole study. There are 120 out of 140 questionnaires were collected from PMINT staffs. The findings in this study were using reliability, descriptive statistics, means and standard deviations and also correlation. The results shows there is a significant relationship between mobile application usages and job performance.